Pengaruh Media Papan Berpaku Terhadap Pemahaman Konsep Luas Bangun Datar Siswa Kelas 3 Sekolah Dasar Islam Terpadu Syifaurrahmah - Rahma, Fitriani; Wandini, Rora Rizki (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research examines the influence of nailed board media on understanding the concept of area of flat shapes in class 3 at SDIT Syifaurrahmah. This research uses a quantitative type of research with a nonequivalent control group design pretest posttest design. Where class 3 has 82 students, with a research sample consisting of 54 students, namely class A and class B. The class consists of 27 students in class 3A 27and 27 students in class 3B. Based on the result of the analysis of grade data and teacher interviews, the researcher considered that class 3A needs to get treatment that will be used as an experimental group, because the average grade of class 3A needs to get treatment that will be used as an experimental group, because the average grade of class 3A is lower than class 3B. The research instruments used were interviews and tests. The data used used the comparison test and paired sample T test. The results of this research were the pretest score was 32.89, while the average posttest score was 80.26, so this shows that there was an improvement after using nailed board media. With the media of the nailed board, learning becomes more fun and students more easily understand the material, especially the wide shapes of flat shapes.